2006
DOI: 10.1111/j.1349-7006.2006.00186.x
|View full text |Cite
|
Sign up to set email alerts
|

MTA1 overexpression correlates significantly with tumor grade and angiogenesis in human breast cancers

Abstract: F emale breast cancer is a major public health problem, with more than 1 000 000 cases occurring worldwide annually. (1) Despite major advances that have been made in understanding the biological and clinical nature of the disease, the therapeutic problem persists. Therefore, identification of novel breast cancer biomarkers could be utilized as possible therapeutic targets or prognostic predictors that would contribute to the advancement of breast cancer treatment.Metastasis associated antigen 1 (MTA1) was ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
73
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 31 publications
5
73
0
Order By: Relevance
“…Multiple studies have shown a correlation between loss of BRCA1 expression and increased metastatic disease. In the light of these findings and because MTA1 is widely overexpressed in human cancers including breast cancer (Toh et al, 1994;Nawa et al, 2000;Jang et al, 2006), and its overexpression has been associated with metastasis, it appears that the MTA1-containing NuRD complex exerts a repressive effect on BRCA1 expression. Consistent with this notion was the relatively significant decrease in the mRNA and protein levels of BRCA1 and its target PARP1 that we observed in MCF7/MTA1 stable cells stably when compared with control MCF7/pcDNA cells (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have shown a correlation between loss of BRCA1 expression and increased metastatic disease. In the light of these findings and because MTA1 is widely overexpressed in human cancers including breast cancer (Toh et al, 1994;Nawa et al, 2000;Jang et al, 2006), and its overexpression has been associated with metastasis, it appears that the MTA1-containing NuRD complex exerts a repressive effect on BRCA1 expression. Consistent with this notion was the relatively significant decrease in the mRNA and protein levels of BRCA1 and its target PARP1 that we observed in MCF7/MTA1 stable cells stably when compared with control MCF7/pcDNA cells (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, MTA1 is overexpressed in a variety of human cancers including cancers of the breast, ovary, lung, gastrointestinal system and colorectum (Toh et al, 1994(Toh et al, , 1999Hamatsu et al, 2003;Balasenthil et al, 2006;Jang et al, 2006;Martin et al, 2006). It also plays an important role in metastasis and tumor aggressiveness (Toh et al, 1994(Toh et al, , 1999Jang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30] MTA1 plays an important role in the adverse course of various human cancers, including breast, prostate, lung, colorectal, gastric, and esophageal cancers, through migration and invasion of cancer cells toward surrounding and distant tissues. [17][18][19][20][21][22][23][24] In HCC, only a small number of studies have examined the role of MTA1 in vascular invasion and survival after treatment. Moon et al 25 reported that high MTA1 expression levels were correlated with large tumors and vascular invasion, based on analysis of paraffin sections from 45 HCC specimens.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Thus, it has been reported that MTA1 overexpression is closely correlated with an aggressive course in several human cancers, such as breast, prostate, colorectal, gastric, and esophageal cancers. [17][18][19][20][21][22][23][24] However, few data are available regarding the role of MTA1 in invasion, recurrence, and survival in HCC patients. 25,26 In this study, we examined whether the high expression levels of MTA1 in HCC tissues can affect the recurrence of HCC after surgical resection and consequently affect patient survival.…”
mentioning
confidence: 99%
“…It is known that MTA1 has important and critical roles in the angiogenesis and progression of a wide variety of cancers. Several studies have identified various roles for MTA1 in normal mammary gland development and human breast cancer progression, including cell proliferation and invasiveness [8]. MTA1 also enhances angiogenesis by stabilization of HIF-1α [9].…”
Section: Introductionmentioning
confidence: 99%